(3eMGSHI GdTQcGJ (B:s (3JMdjd GdfXe h GdeTGcd GdeMGSHjI (B/s - (3eUWai, ceGd GdOjfs; (3SejQ, eMeO hBNQhfs ((3GdEScfOQjI(B: s (3OGQ GdcJGH GdMOjK(B, s, 2008)
(3jVe GdeTGcd GdeMGSHjI GdeYGUQI, WHjYI GdfXGe GdeMGSHj hYfGUQg, EYOGO GdbhGFe GdeGdjI GdeMGSHjI Yf GdaQhY GdeMdjI, GdeMGSHI Yf GdeYGedGJ HGdYedI GdCLfHjI, JQLeI GdbhGFe GdeGdjI GdebGSI HGdYedI GdCLfHjI, GdJUeje GdeMGSHj GdYGe aj GdLeghQjI GddHfGfjI, GdedGeM GdQFjSjI ddJUeje GdeMGSHj GdYGe, eLGdGJ GdJhMjO hGdEdJRGe aj GdJUeje GdeMGSHj GdYGe, GdejRGfjI hab GdfXGe GdeNJUQ, MSGHGJ GdfJjLI habG ddfXGe GdeNJUQs
Keywords: (3GdTQcGJ(B- (3eMGSHIs; (3GdeMGSHIs